Le paysage comme fragmentation de l'Esthetique de la nature a l'Epoque contemporaine. Les experiences poetiques de zanzotto, jaccottet at heaney - Gaio, Daniele <1982> (Alma Mater Studiorum - Università di Bologna, 2014)
In this work, we have considered the theme of landscape in the poetry of Andrea Zanzotto, Philippe Jaccottet and Seamus Heaney within the perspective of a fragmentation of the aesthetics of nature. To that end, the most advanced theories of aesthetics applied to nature, such as environmental Aesthetics and Aesthetik der Natur (also known as ökologische Aesthetik) have been taken into account. The philosophical perspective of Paolo D’Angelo, insights from geography (in particular from the works of Franco Farinelli) and from ecology (considering the contributions of Gilles Clément to this discipline) have also been useful. We have argued that the poetic experiences of Zanzotto, Jaccottet and Heaney follow a similar path, each starting from the fusion between the poetic subject and landscape to reach a two-way relationship between them. In this interpretation, the concept of landscape has been considered, according to Michel Collot’s theory of pensée-paysage, as a phenomenon.